Requiem - Oliver, Lauren, 1982- (New York : Harper, 2013)
"While Lena navigates the increasingly dangerous Wilds, her best friend, Hana, lives a safe, loveless life in Portland"--Provided by publisher.
Keywords: Government, Resistance to -- Juvenile fiction; Love stories; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Marriage -- Juvenile fiction; Maine -- Juvenile fiction; Science fiction